The future of defence rights in the light of the mcdonaldisation of criminal justice systems - Sutton, Pierre-Louie (Vilnius University Open Series, 2023)
Alongside the process of globalisation, from which no state can escape today, there appears to be an underlying “Americanisation of the world”, which is reflected essentially in the worldwide export of American industry and capital, but also of ideas, customs, and social habits. Among these habits, the American sociologist George Ritzer has highlighted the spread of fast-food chains which, according to him, is less a sign of the generalisation of a way of consuming than the implementation of a way of thinking. Indeed, Ritzer observed that contemporary societies have gradually abandoned the traditional way of reasoning in favour of more rational ways of thinking, similar to fast food chains, which rely on efficiency, calculability, predictability and the use of new technologies. Described as “McDonaldisation”, in reference to the famous multinational fast-food corporation, this phenomenon of rationalisation is affecting “more and more sectors of American society as well as the rest of the world” due to cultural homogenisation resulting itself from globalisation. Indeed, the American justice system as well as “the rest of the world”, such as many European legal systems, are also concerned by it, particularly regarding their criminal procedures, which are increasingly under the influence of this process of “McDonaldisation”. The relatively recent use of guilty pleas for individuals and legal persons, the use of sentencing guidelines and the increase in predictive justice in criminal matters reflect the key aspects of “McDonaldisation” mentioned above, namely efficiency, calculability, predictability, and the use of new technologies. However, this streamlining trend harms the defence rights placed at the heart of criminal procedures in general, such as the right to a fair trial, the right to an independent and impartial tribunal, the presumption of innocence and the individualisation of punishment.This paper therefore examines the future of these fundamental rights in the light of the “McDonaldisation” of criminal justice in America and in various European States and focus on the new principles that now guide it.